Does real-time and perceived environmental exposure to air pollution and noise affect travel satisfaction? evidence from Beijing, China. (July 2021) - Ma, Jing; Liu, Guanqiu; Kwan, Mei-Po; Chai, Yanwei
Highlights: Transportation mode affects micro-environmental exposure and travel satisfaction. Different social groups bear unequal burden of air pollution and noise during daily travels. Air pollution and noise influence travel satisfaction through different pathways. Socio-economic variables mainly explain the variations in life satisfaction rather than momentary wellbeing. Abstract: Poor air quality and noise pollution have become major environmental risks in urban China. However, the effect of personal exposure to air pollution and noise in various traffic microenvironments on individuals' daily travel satisfaction has rarely been investigated. Drawing upon real-time data collected using portable sensors and GPS tracking devices in Beijing from December 2017 to February 2018, this paper explores the variations in the co-exposure to real-time air pollution and noise among various transportation modes. It then employs structural equation models to investigate whether and how the objectively measured and subjectively perceived exposure to air pollution and noise in different traffic microenvironments influences individuals' daily travel satisfaction. Findings show that travel satisfaction and co-exposure to real-time air pollution and noise vary greatly among different transportation modes. People travelling by public transport experience high personal noise exposure and tend to have lower levels of travel satisfaction. While perceived air pollution and noise have significant direct effects on travel experiences, the pathways between objective pollution and travel satisfaction differ for air pollution and noise. Objective air pollution negatively affects travel satisfaction indirectly by influencing perceived air pollution, whereas objective noise has a positive and direct effect on travel satisfaction. Moreover, people with different socio-economic backgrounds tend to bear unequal burdens of air pollution and noise during their daily travels. These findings indicate that more research should be conducted to enhance our understanding of the relationships between personal micro-environmental exposures and subjective wellbeing.